SAT0172 Comparison of Efficacy and Safety of Biologic Agents between Elderly-Onset and Younger-Onset Rheumatoid Arthritis. (15th July 2016) - Fujita, K.; Yamamura, Y.; Nomura, Y.; Shibutou, N.; Ueno, A.; Maruyama, K.; Ombe, T.; Hiramatsu, M.; Yamamura, M.
Abstract : Background: There are pathogenetic and clinical differences between elderly-onset rheumatoid arthritis (EORA) and young-onset rheumatoid arthritis (YORA). Objectives: To compare the efficacy and safety of biologic agents between patients with EORA and those with YORA. Methods: A total of 61 patients with RA, who started biologic agents after the age of 65 years, have been enrolled from April 2011 to August 2015, and divided into two groups according to the age at disease onset; i.e. EORA ≥65 years and YORA <65 years. Biologic agents were grouped into 3 classes; the TNF-alpha inhibitors (TNFi) including infliximab, etanercept, adalimumab, golimumab and certolizumab pegol, the CTLA4-Ig abatacept (ABT) and the IL-6 inhibitor tocilizumab (TCZ). Forty-four patients with EORA have received 64 biologic agents (36 women and 8 men; average ± SD age, 76.1 ± 5.7 years; disease duration, 2.0 ± 3.4 years; rheumatoid factor (RF)/anti-cyclic citrullinated peptide antibody (ACPA) positive, 63.6%/65.9%), and 17 patients have received 29 biologic agents (13 women and 4 men; average age, 71.2 ± 4.9 years; disease duration, 17.8 ± 13.9 years; RF/ACPA positive, 76.5%/70.6%). The disease activity was measured according as simplified disease activity index (SDAI), and the efficacy was determined by the induction rate of remission (SDAI ≤3.3) and low-disease activity (3.3 < SDAI ≤11). Results: The EORA patient group did respond better to biologic agents than the YORA patient group; the SDAI was significantly lower in the former than in the latter. At present, there were no significant differences in responses to TNFi, ABT and TCZ between the 2 patient gourps (Table 1 ). Both patient groups developed adverse events during biologic therapy, and severe adverse events including cholecystitis, pulmonary cryptococcosis, diverticulitis, malignant lymphoma, Pneumocystis pneumonia, organizing pneumonia and so on. Conclusions: The results indicate that biologic agents are similarly effective for both EORA and YORA patients, irrelevant to different classes, but patients with EORA appears to be more responsive to biologics than YORA patients, presumably due to their shorter disease duration. Disclosure of Interest: None declared